Combination of Two Nonlinear Techniques Applied to a 3-DOF Helicopter. (17th April 2014) - Ahmadi, P.; Golestani, M.; Nasrollahi, S.; Vali, A. R.
Abstract : A combination of two nonlinear control techniques, fractional order sliding mode and feedback linearization control methods, is applied to 3-DOF helicopter model. Increasing of the convergence rate is obtained by using proposed controller without increasing control effort. Because the proposed control law is robust against disturbance, so we only use the upper bound information of disturbance and estimation or measurement of the disturbance is not required. The performance of the proposed control scheme is compared with integer order sliding mode controller and results are justified by the simulation.